المسؤلية التقصيرية في مهنة الطب العلاجي - Asmuni Muhammad Thahir (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2004)
As a comprehensive religion, Islam draws up the general teaching and rule relating with healthy. This teaching or rule becomes mujtahid’s reference in maintaining the doctor's medical responsibility toward their patient. In this article, the author explains that according to ulama', the responsibility is placed on the doctor because of his carelessness in performing his profession. Whereas other opinion states that the responsibility is caused by the existence o f contract between medical patient and hospital. In relation with operation, the author also explains that according to fuqaha’, the doctor can be free of any responsibilities if he fulfills two requirements both, that the operation was carried out by professional doctor and didn't overstep the normal bounds like cutting something not to do.